Knowledge of menstrual hygiene management among adolescent girls: what does evidence show? - Shrestha, Niki; Dangal, Ganesh; Khanal, Gayatri; Bhandari, Tulsi Ram (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To explore the knowledge of menstrual hygiene management among adolescent girls in different domains like culture, social learning and belief. Methods: This review paper explored the knowledge of menstrual hygiene management under several domains. Literature published in Pub Med, Medline, Google Scholar and HINARI from 2010 to 2020 was reviewed to prepare this paper. Results: The studies revealed that there is a general silence about menstruation. Adequate and accurate information about menstruation and the need for good menstrual hygiene management is limited. It further revealed that girls are not provided with comprehensive information before menarche while growing up, and therefore the first experience of menstruation is without any preparation and usually comes as a shock. Menstruation is widely regarded as a curse from God or as a disease or as being impure or as a taboo. Schools are doing very little to impart education on Menstrual Hygiene Management to adolescents. A majority of the teachers themselves are least or unprepared to address this issue with the girls, even when it is part of the school curriculum. The studies provide a wealth of information for designing interventions to improve menstrual hygiene management. Conclusions: Young girls are not well aware of the menstrual event and the hygienic measures. They are neither well informed nor properly taught by elders and teachers. Effective interventions must be contextualized, designed, and implemented to generate awareness and change the mindset of people surrounding menstruation. Keywords: adolescents, knowledge, menstrual hygiene management, reproductive health